THE CORRELATION BETWEEN STUDENT’S MOTIVATION AND THEIR READING COMPREHENSION AT ELEVENTH GRADE OF SMAN 1 RAJABASA - Safitri, Ketut; Wahyudin, Achmad Yudi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
There are many factors that can influence reading comprehension. Reading motivation and comprehension are two key aspects in creating successful readers. The purpose of this study is to investigate the correlation between student’s motivation and their reading comprehension at eleventh grade of SMAN 1 Rajabasa and to find out the problems faced by the students during the reading process. 30 students of class 11 Merdeka 2 were sampled for data collection. Data were collected using the MRQ questionnaire, reading test and interview. Pearson product moment correlation was used to determine the correlation and strong relation between student’s motivation and reading comprehension which was 0.685. Then, the interview data shows that there are several problems that usually faced by students, such as vocabulary with double meaning and also a noisy environment.